2017
DOI: 10.5005/jp-journals-10024-2151
|View full text |Cite
|
Sign up to set email alerts
|

Post-insertion Posterior Single-implant Occlusion Changes at Different Intervals: A T-Scan Computerized Occlusal Analysis

Abstract: Aim:The aim of this prospective cohort study was to evaluate the postinsertion posterior single-implant occlusion changes at 3-and 6-month intervals using T-Scan computerized occlusal analysis. Materials and methods:A total of 21 patients received single implant, opposed by natural dentition, in posterior regions of the maxilla or mandible (13 premolar, 8 molar) and were finally restored with cemented-retained metal-ceramic crowns. The occlusal contacts were equilibrated according to the implantprotective occl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 26 publications
1
6
0
2
Order By: Relevance
“…The average bite force between contralateral teeth and implant crowns decreased from 3.48 initially to 1.50 times and from 4.54 to 3.09 times for distal teeth and implant crowns over time (Table 7, Fig 8), respectively. The findings of this study were consistent with related research [9,16,29,30], which presented bite force of prosthesis increased from 4.72% to 9.64% at 3 months [29] whereas there was no significant difference in bite force of prosthesis from 3 months (9.87 ± 6.79%) to 6 months (10.59 ± 6.59%) [9]. The continuous eruption of the opposing teeth and the occlusal wear of the remaining natural teeth [31] may partly explain the variation in the occlusion of implant prostheses.…”
Section: Plos Onesupporting
confidence: 93%
See 2 more Smart Citations
“…The average bite force between contralateral teeth and implant crowns decreased from 3.48 initially to 1.50 times and from 4.54 to 3.09 times for distal teeth and implant crowns over time (Table 7, Fig 8), respectively. The findings of this study were consistent with related research [9,16,29,30], which presented bite force of prosthesis increased from 4.72% to 9.64% at 3 months [29] whereas there was no significant difference in bite force of prosthesis from 3 months (9.87 ± 6.79%) to 6 months (10.59 ± 6.59%) [9]. The continuous eruption of the opposing teeth and the occlusal wear of the remaining natural teeth [31] may partly explain the variation in the occlusion of implant prostheses.…”
Section: Plos Onesupporting
confidence: 93%
“…The sample size was calculated according to the experimental research method, and the analysis index was “the change in the bite force distribution with a single posterior implant restoration pre- and post-insertion,” assuming that bite force was the data to be measured [ 16 , 27 ]; an average increase of 2 units of bite force after insertion was considered to be significant if the standard deviation of the difference in the bite force for the subjects in the study was σ = 3 units, α was 0.05 on both sides, and the test efficiency 1-β was 0.90. Then, the standard deviation of the sample bite force s = (σ =) 3 units, δ = 2 units of bite force change, α = 0.05, and = 1.96, β = 0.10, Z β = 1.282 were calculated to obtain 23.65, that is, at least 24 subjects needed to conduct pre- and post-experimental comparisons.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study also reported that the implant-opposing natural dentition continued to erupt so that contact with the implant-supported prosthesis was established. 26 Occlusal wear of the natural teeth may facilitate these changes to some extent, especially before occlusal contacts were established in implant prostheses. The wear of natural teeth, which varies from person to person, is related to personal eating habits and food categories.…”
Section: Discussionmentioning
confidence: 99%
“…Madani et al 26 evaluated the postinsertion posterior single-implant occlusion changes at 3-and 6-month intervals by using the T-Scan computerized occlusal analysis system. They reported that the relative forces at the 6-and 3-month follow-up appointments were significantly higher than those at prostheses insertion.…”
Section: Discussionmentioning
confidence: 99%